2022
DOI: 10.1152/ajpheart.00287.2022
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy attenuates endothelial dysfunction in hypertensive rats with heart failure and preserved ejection fraction

Abstract: Heart failure with preserved ejection fraction (HFpEF) is defined by increased left ventricular (LV) stiffness, impaired vascular compliance and fibrosis. Although systemic inflammation, driven by comorbidities, has been proposed to play a key role, the precise pathogenesis remains elusive. To test the hypothesis that inflammation drives endothelial dysfunction in HFpEF, we used cardiosphere-derived cells (CDCs), which reduce inflammation and fibrosis, improving function, structure and survival in HFpEF rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…However, it is unclear whether volume overload activates the renal sympathetic nerve, helps excrete the exosomes containing erythropoietin (EPO), and increase the regeneration capacity of the heart. Recently, Marban and colleagues have shown that cell therapy preserves ejection fraction (EF) via the vascular endothelium [26]. Here we show that renal denervation preserves ejection fraction via endocardial endothelium.…”
Section: Of 11supporting
confidence: 56%
“…However, it is unclear whether volume overload activates the renal sympathetic nerve, helps excrete the exosomes containing erythropoietin (EPO), and increase the regeneration capacity of the heart. Recently, Marban and colleagues have shown that cell therapy preserves ejection fraction (EF) via the vascular endothelium [26]. Here we show that renal denervation preserves ejection fraction via endocardial endothelium.…”
Section: Of 11supporting
confidence: 56%
“…CDCs treatment improved EC-dependent vasodilation, reduced oxidative stress, restored endothelial NOS (eNOS) expression, previously shown to be decreased in the HFpEF endothelium ( 31 ), inflammatory response and VCAM-1 expression. It also improved diastolic dysfunction and restored vascular reactivity ( 30 ). These results uncover the importance of microvascular dysfunction in HFpEF.…”
Section: Vascular Contribution To Hfpefmentioning
confidence: 98%
“…Recently, using cell therapy, de Couto et al, ( 30 ) administered intracoronary cardiosphere-derived cells (CDCs) during two weeks to HFpEF rats, developed by feeding Dahl salt-sensitive rats with a high salt diet. CDCs treatment improved EC-dependent vasodilation, reduced oxidative stress, restored endothelial NOS (eNOS) expression, previously shown to be decreased in the HFpEF endothelium ( 31 ), inflammatory response and VCAM-1 expression.…”
Section: Vascular Contribution To Hfpefmentioning
confidence: 99%
“…Again, no effects on arterial pressure were observed. Experimental cell therapy with cardiosphere-derived cells (CDCs) improved endothelial function by enhancing nitric oxide production and inhibiting expression of endothelial pro-inflammatory molecules like Vascular cell adhesion protein 1 [39]. CDCs also decreased levels of IL-6 and IL-1b and protected from hypertension induced cardiac damage, without affecting arterial pressure.…”
Section: Immune Targets In Treatment Of Hypertensionmentioning
confidence: 99%